The Influence of Brand Image, Product Quality and Promotion on The Purchasing Decision of Tofu Kopeci - Syahid Amrillah; M Adjie Brio Pratama; Fergiansyah Djuliana; Achmad Faqih; Siti Aisyah (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Consumers in making a decision to buy a product the consumer always considers matters concerning price, packaging, quality, and service. Purchasing decision is an action taken by a consumer to determine a choice from several alternatives available to solve a problem. Customer satisfaction is the level of feeling after comparing perceived performance/results with expectations. So the level of satisfaction is a function of the difference between perceived performance and expectations. If the performance is below expectations, then the customer will be disappointed, if kineja matches or exceeds expectations, then the customer will be very satisfied. The location of the research was carried out at the Cikentrungan Youth Cooperative (Kopeci). Located on Jalan Veteran Kuningan. The research began from May to June 2023 with the object of research, namely Kopeci tofu consumers with a sample of 60 respondents. The design in this study used quantitative methods with data collection using questionnaire instruments. The data used are primary data and secondary data. The data analysis used is descriptive analysis, multiple linear analysis, t test analysis, f test analysis and coefficient of determination. The results showed that: (1) Brand image, product quality, and promotion partially had a positive and significant effect on purchasing decisions. This means that if brand image, product quality, and promotion are improved, it will increase purchasing decisions on tofu kopeci, and (2) There is a simultaneous influence of variables of brand image, product quality and promotion on the decision to buy tofu kopeci. This means that if brand image, product quality and promotion are improved it will improve purchasing decisions on Kopeci tofu.